Polyaniline mixed LB films exposed to X-rays - Malmonge, J. A.; Dhanabalan, A.; Riul, A.; Faria, R. M.; Oliveira, O. N. (Elsevier B.V., 1999)
X-ray irradiation is shown to affect electronic properties of polyaniline (PANi) in composite Langmuir-Blodgett (LB) films of PANi and cadmium stearate, in a similar way to acid doping. The time it takes for the shift in the UV-vis spectra, characteristic of PANi doping, increases linearly with the film thickness, thus indicating a surface-controlled process. The humidity of the environment under which the films are irradiated is also of extreme importance. No shin is observed under vacuum or under dry atmospheres of N-2, O-2 and Ar. For humid environments the time for the shift decreases with increasing relative humidity.
Keywords: Langmuir-Blodgett technique; UV-Vis spectroscopy; polyaniline